Reliabilities of Genomic Prediction for Young Stock Survival Traits Using 54K SNP Chip Augmented With Additional Single-Nucleotide Polymorphisms Selected From Imputed Whole-Genome Sequencing Data - Gebreyesus, Grum; Lund, Mogens Sandø; Sahana, Goutam; Su, Guosheng (Frontiers in Genetics, 2021)
This study investigated effects of integrating single nucleotide polymorphisms (SNPs) selected based on previous genome-wide association studies (GWAS), from imputed whole genome sequencing (WGS) data, in the conventional 54K chip on genomic prediction reliability of young stock survival traits in dairy cattle. The WGS SNPs included two group of SNP sets that were selected based on GWAS in the Danish Holstein for young stock survival index (YSS_SNPs, n =98) and SNPs chosen as peaks of quantitative trait loci for the traits of Nordic total merit index in Denmark–Finland–Sweden dairy cattle populations (DFS_SNPs, n = 1541). Additionally, the study also investigated possibility of improving genomic prediction reliability for survival traits by modelling the SNPs within recessive lethal haplotypes (LET_SNP, n=130) detected from the 54K chip in the Nordic Holstein. De-regressed proofs (DRPs) were obtained from 6558 Danish Holstein bulls genotyped with either 54K chip or customized LD chip that includes SNPs in the standard LD chip and some of the selected WGS SNPs. The chip data were subsequently imputed to 54K SNP together with the selected WGS SNPs. Genomic best linear unbiased prediction (GBLUP) models were implemented to predict breeding values either through pooling the 54K and selected WGS SNPs together as one genetic component (a one-component model) or considering 54K SNPs and selected WGS SNPs as two separate genetic components (a two-component model). Across all the traits, inclusion of each of the selected WGS SNP sets led to negligible improvements in prediction accuracies (0.17 percentage points on average) compared to prediction using only 54K. Similarly, marginal improvement in prediction reliability was obtained when all the selected WGS SNPs were included (0.22 percentage points). No further improvement in prediction reliability was observed when considering random regression on genotype code of recessive lethal alleles in the model including both groups of the WGS SNPs. Additionally, there was no difference in prediction reliability from integrating the selected WGS SNP sets through two-component model compared to the one-component GBLUP.